Synthesis and properties of new materials with cobalt(II), iron(III) and manganese(III)-substituted Keggin polyoxotungstates and 1-alkyl-3-methylimidazolium cations - Santos, Filipe M
Several novel compounds with 1 alkyl 3 methylimidazolium cations (alkyl butyl and octyl) and first row transition metal substituted Keggin polyoxoanions were synthesised, having the general formula (cation)m[PW11O39M(H2O)] xH2O or (cation)m 1H[PW11O39M(H2O)] xH2O, M Co, Fe, Mn and m anion charge. All compounds were characterized by spectroscopic and analytical techniques. These studies indi cated that both the polyoxometalates and the cations are present in the solids without major alterations. Cyclic voltammetry studies were performed for compounds with 1 butyl 3 methylimidazolium. Disregarding the loss of crystallization or coordinated water, the compounds were found to be stable up to near 300 C. The onset of the decomposition of the organic cations, as determined by thermo gravimetry, occurred in the 300 350 C range. The metal substituted polyoxoanions are stable up to around 300 C, but after this temperature the anions transform into the parent [PW12O40]3 anion, with loss of the substituting metal. Final decomposition to a mixture of oxides occurred only above 600 C. It was also possible to obtain the crystalline compounds Na2K(Bmim)2[PW11O39Co(H2O)] 7.5H2O and Na(Bmim)4[PW11O39Co(H2O)] 2H2O and determine their structures by single crystal X ray diffraction